Serpent daughter - Butler, D. J. (David John), 1973- (Butler, D. J. (David John), 1973- Witchy eye series, 2021)
"Sarah Calhoun has taken her father's throne and ascended into her goddess's presence in Unfallen Eden as her father never did. But the queen may be dying. Forces are allied against her, from without as well as from within. To survive, Sarah must enact an ancient rite that will propel her beyond mortality and lend her strength to fight. The Queen may be dying, true. But if she is, she will go down fighting for the only thing that matters."--Back cover